2022
DOI: 10.1128/aem.02449-21
|View full text |Cite
|
Sign up to set email alerts
|

Functional Insights of Salinity Stress-Related Pathways in Metagenome-Resolved Methanothrix Genomes

Abstract: Using genome-centric metagenomics, we discovered a new Methanothrix harundinacea subspecies that appears to be a halotolerant acetoclastic methanogen with the flexibility for adaptation in the anaerobic digestion process both at low (5 g/L Na + ) and high salinity conditions (20 g/L Na + ). Annotation of the recovered M. harundinacea genome revealed salinity stress-related functions, including the modification of EP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 117 publications
0
4
0
Order By: Relevance
“…We detected 26 viruses across 25 samples originating from 5 sites (Table 1). These viruses were found in ecosystems where biofilm formation has been evidenced (for example, anaerobic digester sludges 27 , petrochemical wastewater in a tailings pond 28 and a CO 2 -rich subsurface aquifer 29 ) and metabolic interdependencies have been highlighted using various methods such as co-occurrence networks 30 , metatrascriptomics 31 and lipidomics 29 . Additionally, many of the matching CRISPR spacers were found in known or hypothesized syntrophic taxa, such as Methanosarcinales 32 , Methanoculleus 33 , Smithella 34 and Thermotogales 35 (Supplementary Table 17).…”
Section: Global Distribution Of Microbial Domain-crossing Virusesmentioning
confidence: 99%
“…We detected 26 viruses across 25 samples originating from 5 sites (Table 1). These viruses were found in ecosystems where biofilm formation has been evidenced (for example, anaerobic digester sludges 27 , petrochemical wastewater in a tailings pond 28 and a CO 2 -rich subsurface aquifer 29 ) and metabolic interdependencies have been highlighted using various methods such as co-occurrence networks 30 , metatrascriptomics 31 and lipidomics 29 . Additionally, many of the matching CRISPR spacers were found in known or hypothesized syntrophic taxa, such as Methanosarcinales 32 , Methanoculleus 33 , Smithella 34 and Thermotogales 35 (Supplementary Table 17).…”
Section: Global Distribution Of Microbial Domain-crossing Virusesmentioning
confidence: 99%
“…8F). Genome-centric metatranscriptomic data revealed that ectoine is used by Methanothrix_A_harundinacea_D (MAG_5_1) as an osmoprotectant, which potentially enhances cell granulation [84]. The benzoate degradation pathway, which requires elevated expression of enoyl-acyl carrier protein reductase can be linked to the novel mixotrophic methanogen Methanosarcina sp., which we found to be common in SZBP (no species-level representative was found in the GTDB and Biogas Microbiome databases; MAG_165_3).…”
Section: Resultsmentioning
confidence: 99%
“…MB108 (p < 0.05). The activity of ablB was only documented in Methanothrix species until now, 52 thus this is the first time that synthesis of Nε-acetyl-L-lysine was demonstrated also in hydrogenotrophic methanogens.…”
Section: Environmental Science and Technologymentioning
confidence: 88%
“…51 The reduction of acetate in Methanothrix spp. is catalyzed by the Acetyl-CoA synthetase (acs), 52 whose encoding gene showed no change in expression level after the two shocks in Methanothrix sp. MA6.…”
Section: Effect Of Ammonia On the Methanogenic Microcosmmentioning
confidence: 99%